Fault detection and behavioural prediction of a constrained complex system using cellular automata. (2018) - Priya, R.; Sherly, Elizabeth
Functionality-based failure analysis and validation during design process in a constrained complex system is challenging. In this paper, we advocate a model to validate the functionality of a constrained complex control system with its structural behaviour. An object constrained model is proposed for validation of any component of a complex system with constraints and its state of safeness is predicted using cellular automata. The model consists of two sub-systems; an inference engine that functions based on rule-based expert system and a failure forecast engine based on cellular automata. The system is tested against the thermal power plant for early detection of failure in the system which enhances the process efficiency of power generation.